2005
DOI: 10.1093/jmicro/dfh097
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and immunohistochemical studies of medullary bone calcification, with special reference to sulphated glycosaminoglycans

Abstract: Histochemical, immunohistochemical and electron energy-loss spectroscopic studies were performed to examine the relationship between sulphated glycosaminoglycans and medullary bone calcification using oestrogen-injected male Japanese quail. Sulphated glycosaminoglycans, detected by high iron diamine (HID) or HID-thiocarbohydrazide-silver protein (HID-TCH-SP) methods, were distributed throughout the matrix of medullary bone, some periphery and extending tips of the trabeculae stained weakly, and the globular st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…At the ultrastructural level, DPSC show all stages of osteogenesis, starting with MSCs which develop into mature osteocytes. In addition, the secretory activity of differen- tiated DPSC very closely resembles the globular secretion pattern which is seen during in vivo osteogenesis [Yamamoto et al, 2005]. The presence of hydroxyapatite needles confirms the occurrence of real mineralization in the culture.…”
Section: Discussionsupporting
confidence: 66%
“…At the ultrastructural level, DPSC show all stages of osteogenesis, starting with MSCs which develop into mature osteocytes. In addition, the secretory activity of differen- tiated DPSC very closely resembles the globular secretion pattern which is seen during in vivo osteogenesis [Yamamoto et al, 2005]. The presence of hydroxyapatite needles confirms the occurrence of real mineralization in the culture.…”
Section: Discussionsupporting
confidence: 66%
“…To our knowledge, the current study showed for the first time the morphological characteristics and gene modulation of xeno-free hPDLSCs cultured in osteogenic inductive medium. Some differentiation steps of osteogenic cells and, in particular, the secretion of ECM resembling the secretion pattern during in vivo osteogenesis 44,45 were documented.…”
Section: Discussionmentioning
confidence: 97%
“…Organ cultures of medullary bone matrix from female birds and E2‐treated male birds included glycosaminoglycans, such as keratan sulfate and chondroitin sulfate (Fisher and Schraer, ’80; Hunter and Schraer, ’83). Yamamoto et al () demonstrated that these sulfated glycosaminoglycans accumulated in the bone matrix near cortical bone and acted as foci for mineralization, suggesting that they played an important role in the process of medullary bone mineralization. Meanwhile, Wang et al () suggested that the accumulation of keratan sulfate‐containing proteoglycans in the medullary bone matrix contributed to its rapid resorption.…”
Section: Methodsmentioning
confidence: 99%